Sistem Monitoring Instrument Air Compressor (IAC) Berbasis SCADA dengan Komunikasi Modbus RTU RS-485 - Zakaria, Muchamad Chadiq; Kurniawan, Edy; Sulthon H, Jawwad (Universitas Hang Tuah, 2020)
The Pacitan Power Plant is one of the power plants in East Java that has a capacity of 2 x 315 MW which was built by the government in the Fast Track Program 1. The Instrument Air Compressor (IAC) is one of the auxiliary equipment at the Pacitan Power Plant that provides air supply to the factory's advanced pneumatic system. However, this equipment cannot be monitored by the Central Control Room (CCR) operator to the maximum. The parameters that can be controlled are very limited. This is due to the limited number of available Field Bus Module (FBM) terminals. The problem formulation is how to create a communication module to display the parameters of the Air Compressor System Instrument to display the HMI CCR operator in real time. The purpose of designing tool is to create a safe and reliable communication module to display all the parameters of the existing Air Compressors to be displayed in the CCRâ€™s computer display. The method used is the control and transmission parameters that are transmitted from the field to the Central Control Room using serial communication RS485 Modbus Protocol.Â